Plasma vasopressin and response to treatment in primary nocturnal enuresis. Issue 5 (1st May 1999) - Devitt, H; Holland, P; Butler, R; Redfern, E; Hiley, E; Roberts, G
Abstract : AIMS: To examine the relation between nocturnal vasopressin release and response to treatment with the vasopressin analogue 1-desamino-8-D -arginine vasopressin (DDAVP) in children with primary monosymptomatic nocturnal enuresis. DESIGN: Children were recruited from a specific enuresis clinic and entered into a defined treatment programme. Nocturnal vasopressin concentrations were measured every 15 minutes over a four hour period during overnight admission. RESULTS: Sixty seven children were eligible for entry into the study, 35 of whom agreed to overnight sampling. There was a quadratic relation between mean plasma AVP and response to treatment with DDAVP, with very high or very low concentrations being unresponsive. Plasma AVP profiles ranged from low concentrations with little variability to high concentrations with wide variability. CONCLUSION: The ability to respond to DDAVP is related to endogenous AVP production and is influenced by neuronal patterning in early infancy. The best predictors of success with treatment were a past history of breast feeding, mean nocturnal AVP concentration, and the height of the child. The response was adversely affected by poor weight at birth and poor linear growth. The study suggests differing causes of nocturnal enuresis related to different patterns of AVP release.